Diagram of vapor‐liquid equilibria for n‐pentane using hybrid Gibbs ensemble Monte Carlo simulation. Issue 1 (26th February 2020) - Nhung, Nguyen Thi Ai; Van Tat, Pham
Abstract: In this paper we report the simulation results using the 5‐site Lennard‐Jones potential function obtained from ab initio interaction energy for n ‐pentane at level of theory CCSD(T)/aug‐cc‐pVTZ. The hybrid Gibbs ensemble Monte Carlo (HGEMC) simulation was performed under the same initial conditions for boxes 1 and 2 with 60 molecules and a density of 0.130 g /cm 3 . The HGEMC simulation was implemented with 10 6 epochs and value of Cutoff_Radius 10Å. The simulation temperature was varied from 100 to 450 K. The thermodynamic results of the vapor‐liquid equilibria derived from HGEMC‐NVT simulation are consistent with experimental data and other calculation methods.